2021
DOI: 10.1519/jsc.0000000000002922
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Damage–Based Recovery Strategies Can Be Supported by Predictive Capacity of Specific Global Positioning System Accelerometry Parameters Immediately a Post-Soccer Match-Load

Abstract: da Silva, CD, Machado, G, Fernandes, AA, Teoldo, I, Pimenta, EM, Marins, JCB, and Garcia, ES. Muscle damage–based recovery strategies can be supported by predictive capacity of specific global positioning system accelerometry parameters immediately after soccer match-load. J Strength Cond Res 35(5): 1410–1418, 2021—Soccer match-load can be linked to recovery kinetic markers. However, match variability hinders the magnitude of relationship between parameters of interest. Therefore, we examined the correlation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 39 publications
0
13
0
1
Order By: Relevance
“…In the first visit, the athletes were characterized (weight and height) and familiarized using a standardized 90min football-match simulation protocol (FMP) [29,30]. The energetic value of the athletes' habitual intake was determined by registering their usual food diet during three consecutive days, and also including their average weekend consumption [31].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first visit, the athletes were characterized (weight and height) and familiarized using a standardized 90min football-match simulation protocol (FMP) [29,30]. The energetic value of the athletes' habitual intake was determined by registering their usual food diet during three consecutive days, and also including their average weekend consumption [31].…”
Section: Methodsmentioning
confidence: 99%
“…The hydration in FMP occurred with water (2 mL.kg [BW] − 1 ) every 15 min up to 75 min to ensure adequate hydration [32]. FMP was a 90-min fatiguing exercise protocol (T-SAFT 90 ) corresponding to an official football match played from audio commands [29,30]. Each player used a strap equipment component of Polar Team System® (Polar Electro Oy, Kempele, Finland).…”
Section: Methodsmentioning
confidence: 99%
“…A few studies have investigated the relationship between external load variables and recovery from football matches via muscle damage indicators in blood and neuromuscular fatigue measurements (Thorpe and Sunderland, 2012; de Hoyo et al, 2016; Russell et al, 2016; da Silva et al, 2018b). While these studies have reported associations between creatine kinase (CK) and high-intensity running distance, sprint distance, and number of sprints, between myoglobin (MYO) and number of sprints, and between countermovement jump performance (CMJ) and decelerations and accelerations, they are somewhat limited to correlation analyses with small sample sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Seventy-two hours post-match is a key time-point where the next match or a hard training session may take place. Most studies have examined the relationships for only 24–48 h post-match (Thorpe and Sunderland, 2012; de Hoyo et al, 2016; Russell et al, 2016; da Silva et al, 2018b), despite evidence showing substantial changes in recovery markers at 72 h post-match (Ascensão et al, 2008; Ispirlidis et al, 2008). Additionally, due to individual differences in recovery time, some players might be recovered and some players not, hence being able to predict the recovery status on day three post-match is practically important.…”
Section: Introductionmentioning
confidence: 99%
“…Iako je u pitanju nova tehnologija, istaživanja koja su se bavila validacijom uređaja za predviđanje laktatnog praga pokazala su da ovi uređaji mogu biti pouzdan alat za predviđanje vrednosti laktatnog praga kod sportista i na osnovu toga moguće je planirati trenažna opterećenja (Perrey & Ferrari, 2011;Borges & Driller, 2016;Farzam, Starkweather, & Franceschini, 2018;). (Bayliff, Jacobson, Moghaddam, & Estrada, 2019;da Silva et al, 2018;Waldron, Twist, Highton, Worsfold, & Daniels, 2011). Kao predstavnik ove grupe uređaja mogao bi se istaći, već spomenuti OptimEye S5, kompanije Catapult Sports.…”
Section: Informacione Tehnologije U Sportuunclassified